Trace element content and morphological characteristics in microscale of commercially available clays used as cosmetic products - Giouri, K.; Papadopoulos, A.; Bourliva, A.; Tzamos, E.; Papadopoulou, L.; Filippidis, A. (Bulletin of the Geological Society of Greece, 2013)
Two kinds of clays (one white and one green) available in pharmacies and herbalist’s shops in the Greek market have been studied for their concentrations in trace elements, namely As, Be, Cd, Cr, Hg, Ni, P, Pb, Sb, Se, Te, Tl and Zr. According to EC Regulation 1223/2009, the presence of the analyzed trace elements and their compounds, are prohibited in cosmetics. The most abundant trace elements of the white clay are P (330 ppm), Pb (220 ppm) and Zr (11 ppm), while for the green clay are P (1250 ppm), As (43 ppm), Cr (31 ppm), Pb (30 ppm) and Ni (23 ppm). Compared to the global shale average concentration of elements, Pb is enriched 11-times in the white clay and As is enriched 3-times in the green clay. The depleted trace elements of the white clay are As, Cd, Cr, Hg, Ni, P, Sb, Se, Te, Tl and Zr, while of the green one are Cr, Hg, Ni, Sb, Te, Tl and Zr. Concerning the morphological characteristics, differences were observed in the particle size and shape between the white and green clay aggregates.